2007
DOI: 10.1136/bjsm.2006.030767
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tibial positioning on the diagnosis of posterolateral rotatory instability in the posterior cruciate ligament-deficient knee

Abstract: An anterior force applied to the tibia during the dial test in a combined PCL-PLC-injured knee increased the overall amount of observed tibial external rotation during the dial test. The anterior force reduced the posterior tibial subluxation associated with PCL injury, which is analogous to what is observed when the dial test is performed with the patient in the prone position. Reducing the tibia with either an anterior force when the patient is supine or performing the dial test with the patient in the prone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 32 publications
(17 reference statements)
0
27
0
1
Order By: Relevance
“…Non-reduction of the knee in the sagittal plane can block external rotation of the tibia. 23,24 Another advantage, as well as critical detail, of the maneuver for evaluation of the PLC lesion is the use of the position of the anterior edge of the lateral plateau in relation to the lateral femoral condyle and not only external rotation of the tibia, which can be caused by other deviations. Noyes et al 22 show that injuries of the anteromedial complex can cause external rotation during the dial test, whichdif compared with the uninjured sidedmay be erroneously interpreted as a PLC lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Non-reduction of the knee in the sagittal plane can block external rotation of the tibia. 23,24 Another advantage, as well as critical detail, of the maneuver for evaluation of the PLC lesion is the use of the position of the anterior edge of the lateral plateau in relation to the lateral femoral condyle and not only external rotation of the tibia, which can be caused by other deviations. Noyes et al 22 show that injuries of the anteromedial complex can cause external rotation during the dial test, whichdif compared with the uninjured sidedmay be erroneously interpreted as a PLC lesion.…”
Section: Discussionmentioning
confidence: 99%
“…With the supine dial test, Strauss et al [14] showed increased external rotation when the test is performed with the tibiae anteriorly reduced. Jung et al [5] [15] tested this hypothesis in a clinical setting and also found an increase in external rotation translating into improved sensitivity of the test.…”
Section: Discussionmentioning
confidence: 99%
“…The Dial test may be performed with the patient positioned either supine or prone 7,73 and has been shown to have substantial agreement within and between testers. 32 If a PCL-PLC combined injury is suspected, performing the Dial test with the patient in prone or adding an anteriorly directed force to the tibia while testing in the supine position can increase the amount of tibial external rotation observed and would presumably increase the sensitivity of the test.…”
Section: Associated Injuriesmentioning
confidence: 99%
“…32 If a PCL-PLC combined injury is suspected, performing the Dial test with the patient in prone or adding an anteriorly directed force to the tibia while testing in the supine position can increase the amount of tibial external rotation observed and would presumably increase the sensitivity of the test. 32,73 However, sensitivity and specificity values have not been reported for the Dial test. With the patient supine, the knee is flexed off the edge of the examining table to 30° and then 90° with the thigh stabilized against the table.…”
Section: Associated Injuriesmentioning
confidence: 99%
See 1 more Smart Citation